Understanding Gene Involvement in Hepatocellular Carcinoma: Implications for Gene Therapy and Personalized Medicine - Younis MA; Harashima H (Dove Medical Press, 2024)
Mahmoud A Younis,1,2 Hideyoshi Harashima1 1Laboratory of Innovative Nanomedicine, Faculty of Pharmaceutical Sciences, Hokkaido University, Sapporo, 060-0812, Japan; 2Department of Industrial Pharmacy, Faculty of Pharmacy, Assiut University, Assiut, 71526, EgyptCorrespondence: Hideyoshi Harashima, Faculty of Pharmaceutical Sciences, Hokkaido University, Sapporo, 060-0812, Japan, Email harasima@pharm.hokudai.ac.jp Mahmoud A Younis, Faculty of Pharmacy, Assiut University, Assiut, 71526, Egypt, Email mahmoudyounis@aun.edu.egAbstract: Hepatocellular carcinoma (HCC) is the dominant type of liver cancers and is one of the deadliest health threats globally. The conventional therapeutic options for HCC are hampered by low efficiency and intolerable side effects. Gene therapy, however, now offers hope for the treatment of many disorders previously considered incurable, and gene therapy is beginning to address many of the shortcomings of conventional therapies. Herein, we summarize the involvement of genes in the pathogenesis and prognosis of HCC, with a special focus on dysregulated signaling pathways, genes involved in immune evasion, and non-coding RNAs as novel two-edged players, which collectively offer potential targets for the gene therapy of HCC. Herein, the opportunities and challenges of HCC gene therapy are discussed. These include innovative therapies such as genome editing and cell therapies. Moreover, advanced gene delivery technologies that recruit nanomedicines for use in gene therapy for HCC are highlighted. Finally, suggestions are offered for improved clinical translation and future directions in this area of endeavor.Keywords: hepatocellular carcinoma, gene therapy, personalized medicine, nanomedicines, clinical translation